Diversification of Fish-Based Processed Products as an Effort to Improve the Economy of Fishermen in the Sula Islands Regency, North Maluku Province (Agrikan Jurnal Agribisnis Perikanan, 2024)
The aim of the research is to determine the potential of fisheries resources in the Sula Islands Regency and then develop them into processed products with high added value as well as finding the right strategies and innovations to improve the economy of the people in the Sula Islands Regency. The method used in the research was a survey method and at the same time conducting focus group discussions (FGD) and interviews with key informants. The results obtained from the research are that the intensification of fisheries production in the Sula Islands Regency shows a significant positive trend, as evidenced by the dominance of tuna fish production of 82,147 tons (2023), a substantial increase from the 2017-2018 period (3,211.08 tons to 3,587.79 tons), as well as commodity diversification through the development of dried seaweed which reached 8,200 tons; Institutional stratification of fisheries was identified through the dominance of the smoked fish processing industry (26 groups), with heterogeneous spatial distribution in six villages, where Fogi Village recorded the highest concentration (10 groups), indicating the existence of disparities in capacity development between regions Paradigmatic transformation in fisheries resource management,...
Keywords: Tuna; Divesifikasi; produk perikana; ekonomi masyarakat; kepulaun Sula